2015
DOI: 10.1590/1519-6984.06214
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal and predation of Buchenavia tomentosa Eichler (Combretaceae) in a Cerrado sensu stricto, midwest Brazil

Abstract: The ecology of seed dispersal is critical to understand the patterns of distribution and abundance of plant species. We investigated seed dispersal aspects associated with the high abundance of Buchenavia tomentosa in the Serra Azul State Park (PESA). We estimated fruit production and conducted fruit removal experiments. We carried out diurnal and nocturnal observations on frugivory as well as germination tests. Fruiting occurred in the dry season and totaled 1,365,015 ± 762,670 fruits.ha -1 . B. tomentosa fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Non-germination of A. subincanum and T. corrugataspecies in the laboratory may be related to the seed lot, type of photoblastism or low seed storage potential, which can reduce seed viability (e.g., A. subincanum, Oliveira et al 2016). Previous experiments suggest that A. subincanum has optimal germination at 25 ºC and a 12-hour photoperiod (Oliveira et al 2016), while 100 % of T. corrugata seeds can germinate in natural temperature and light conditions (Soares et al 2006;Farias et al 2015). Therefore, regarding treatment homogeneity, the germination test simulating darkness of buried seeds and direct sowing conditions shows that direct seeding strategies must also be heterogeneous in the field.…”
Section: Germination and Average Germination Timementioning
confidence: 99%
“…Non-germination of A. subincanum and T. corrugataspecies in the laboratory may be related to the seed lot, type of photoblastism or low seed storage potential, which can reduce seed viability (e.g., A. subincanum, Oliveira et al 2016). Previous experiments suggest that A. subincanum has optimal germination at 25 ºC and a 12-hour photoperiod (Oliveira et al 2016), while 100 % of T. corrugata seeds can germinate in natural temperature and light conditions (Soares et al 2006;Farias et al 2015). Therefore, regarding treatment homogeneity, the germination test simulating darkness of buried seeds and direct sowing conditions shows that direct seeding strategies must also be heterogeneous in the field.…”
Section: Germination and Average Germination Timementioning
confidence: 99%
“…These authors reported a rate of more than 93% of attacks by this insect in imbuzeiro seeds collected on the ground, which was not observed in the seeds collected directly from the trees. In contrast, Farias et al (2015) studying Buchenavia tomentosa in a Cerrado stricto sensu from the state of Mato Grosso found A. insuturatus larvae in fruit collected in the trees, indicating a pre-dispersion attack. In the same study, the authors also observed signals of emergence of the adult insects, characterized by the endosperm and embryo completely consumed.…”
Section: Resultsmentioning
confidence: 85%
“…tomentosa is native from Cerrado and Amazon Rainforest. In the first biome, the trees begin to fruit in March, and the dispersal starts in June (Farias et al, 2015); whereas in the second one, the fructification begins in September, with dispersion in May (Camargo et al, 2008). At Cerrado, due to the occurrence of a well-defined dry season and short water during a long part of year (Figure 1), the seeds are able to germinate only at the time of water availability, which coincides with the period of high average temperatures (Brancalion et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…tomentosa presents intense fruit production, important for the maintenance of Cerrado's flora and fauna, and the fruits are efficiently propagated by several animals, such as ants, deer and mainly by tapir, which consume the pulp. On the tapir's case, the seeds pass through the digestive tract, favors the removal of pulp adhered to the fruits and does not affect the germination potential (Farias et al, 2015). The dispersers can still contribute to the endocarp's remover and faster species populations' formation at Cerrado.…”
Section: Introductionmentioning
confidence: 99%